2018
DOI: 10.1021/acsami.8b12694
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and Reversal of Skyrmion Lattice in Ta/CoFeB/MgO Multilayers

Abstract: Recently, magnetic skyrmion has attracted much attention due to its potential application in racetrack memory and other nanodevices. In bulk chiral magnets with non-centrosymmetric crystal structures, skyrmion lattice phase has been extensively observed. However, in film or multilayers with interfacial Dzyaloshinskii–Moriya interaction, individual skyrmion is often observed. Here, we report a short-ordered skyrmion lattice observed in [Ta­(5.0 nm)/CoFeB­(1.5 nm)/MgO­(1.0 nm)]15 multilayer in a remnant state. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…In this first series of images, the number of magnetic skyrmions is low. To obtain more magnetic skyrmions, the sample was saturated in an in-plane direction, as reported in previous studies (Qin et al, 2018;Li et al, 2020). The in-plane magnetic field was applied in situ in the TEM by tilting the sample to 80°and exciting the conventional microscope objective lens fully (corresponding to an applied magnetic field of approximately 1.4 T) for a few seconds.…”
Section: Magnetic and Crystalline Structure Of The Samplementioning
confidence: 99%
“…In this first series of images, the number of magnetic skyrmions is low. To obtain more magnetic skyrmions, the sample was saturated in an in-plane direction, as reported in previous studies (Qin et al, 2018;Li et al, 2020). The in-plane magnetic field was applied in situ in the TEM by tilting the sample to 80°and exciting the conventional microscope objective lens fully (corresponding to an applied magnetic field of approximately 1.4 T) for a few seconds.…”
Section: Magnetic and Crystalline Structure Of The Samplementioning
confidence: 99%
“…In particular, a high-density skyrmion phase is instrumental for the realization and optimization of theoretically proposed unconventional skyrmion-based computing models (e.g., probabilistic computing, reservoir computing) [25][26][27] . Note that although there is a report on skyrmion lattices observed in magnetic multilayers 28 , isolated skyrmions have been the norm in most magnetic multilayer systems, raising questions about the widespread application of multilayer-based ultrahigh-density skyrmion memory and computing devices.…”
Section: Introductionmentioning
confidence: 99%
“…The key to achieve a perpendicular-anisotropy CoFeB/MgO MTJ is the very thin thickness of CoFeB layer. 23,24 The PMA was attributed entirely to the CoFeB-MgO interfacial anisotropy by Ikeda et al, 8 while the Ta seed layer, not just the MgO at the top interface, was demonstrated to be critical to achieving perpendicular magnetic anisotropy. 25 The microscopic origin of the PMA in the CoFeB/MgO structure is still far from clear.…”
Section: Introductionmentioning
confidence: 99%